Acute small bowel obstruction due to ileal endometriosis: a case report and review of the most recent literature - UNALP, Haluk Recai; AKGUNER, Taner; YAVUZCAN, ALİ; EKINCI, Neşe (Vojnosanitetski pregled, 2012)
Introduction. Endometriosis is defined as the presence of benign endometrial glands and stroma outside the normal anatomical location. Endometriosis of the small bowel, especially symptomatic small bowel involvement, is very unusual. Case report. We presented a 45-year-old woman with acute intestinal obstruction due to ileal endometriosis The patient complained of severe abdominal pain, nausea and vomitting. Immediate laparotomy was carried out. Above the ileocecal valve there was an ulcerated, edematous and fragile segmental lesion that caused intestinal obstruction. Histology of this ileal segment revealed endometriosis and an annular stricture that again showed foci of endometriosis. Conclusion. In reproductive-age women with the symptoms of intestinal obstruction, intestinal endometriosis should be kept in mind. Key words:       ileum; intestinal obstruction; endometriosis; abdomen, acute; diagnosis; surgical procedures, operative; treatment outcome.